The Integration Model of 2013 Curriculum and Cambridge Curriculum in Elementary Schools - Uswatun Hasanah (IAIN Syekh Nurjati Cirebon, 2019)
AbstractThis study aims to describe the integration model of 2013 curriculum and Cambridge curriculum as well as its implementation and the impacts of its integration in elementary schools. Involving an ICP class of Universitas Negeri Malang (UM) elementary laboratory school and a model class of Brawijaya Smart School elementary school, a qualitative case-study method and a multi cases design were employed in this study. The data were collected from observations, interviews, and documentations which then analyzed using an interactive analysis model. The result of the study shows that (1) the integration of 2013 curriculum and Cambridge curriculum in the Brawijaya Smart School elementary school uses a model of Sequenced Eye-glasses integration, while a Shared Binoculars Integration model is used in the UM elementary lab school; (2) The implementation of Sequenced Eye-glasses in the model class of the Brawijaya Smart School elementary school is conducted by compiling and teaching the materials from both curricula. Meanwhile, a Shared Binoculars Integration model in UM elementary lab school is implemented through teaching the 2013 curriculum thematically and the Cambridge curriculum separately. (3) The integration of 2013 curriculum and Cambridge curriculum enhances students' abilities in: a) English language; b) reasoning; c) creative thinking; and d) academic achievements.Keywords: integrated curriculum model, 2013 curriculum, Cambridge curriculum. AbstrakPenelitian ini bertujuan untuk mendeskripsikan model integrasi kurikulum 2013 dan kurikulum Cambridge beserta implementasinya, dan dampak integrasi tersebut pada sekolah dasar. Melibatkan satu kelas ICP (SD Laboratorium Universitas Negeri Malang) dan satu kelas model (SD Brawijaya Smart School), pendekatan kualitatif metode studi kasus dengan rancangan multikasus digunakan pada penelitian ini. Data diperoleh melalui observasi, wawancara, dan dokumentasi dan kemudian dianalisis dengan model analisis interaktif. Hasil penelitian menunjukkan bahwa (1) integrasi kurikulum di kelas Model SD Brawijaya Smart School menggunakan model integrasi Sequenced Eye-glasses, sedangkan model integrasi Shared Binoculars Integration digunakan di kelas ICP SD Laboratorium Universitas Negeri Malang; (2) Implementasi model Sequenced Eye-glasses dilaksanakan dengan menyusun materi dari dua kurikulum tersebut, dan mengajarkan materi yang berkaitan secara bersamaan. Implementasi model Shared Binoculars Integration dilaksanakan dengan mengajarkan Kurikulum 2013 secara tematik dan Kurikulum Cambridge secara terpisah. (3) Integrasi kurikulum 2013 dan kurikulum Cambridge dapat meningkatkan a) kemampuan berbahasa Inggris; b) kemampuan dalam bernalar; c) kemampuan berpikir kreatif; dan d) prestasi akademik.Kata kunci: model integrasi kurikulum, kurikulum 2013, kurikulum Cambridge.